2022
DOI: 10.1186/s43093-022-00139-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of supervisor work-life support on the correlation between work autonomy, workload and performance: perspective from Tanzania banking employees

Abstract: This research aims to assess the influence of supervisor work-life support on bank employees' performance linking work autonomy and employee workload in this relationship. A survey was conducted among bank employees in the Central Zone regions of Tanzania. Bank workers completed 417 survey questionnaires in total. The data was then analysed using structural equation modelling. The researchers use Smart PLS, a data analysis tool, to see if there are any theoretically supported connections between variables of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Rohman's research (2021) shows that workload positively and significantly affects the performance of PT Honda Daya Anugrah Mandiri Sukabumi Branch employees. The same thing was expressed by research by Msuya and Kumar (2022), which states that workload has a positive and significant effect on the performance of bank employees in Tanzania. The results of this research mean that the increasing employee workload will cause employee performance to increase as well.…”
Section: Introductionmentioning
confidence: 52%
“…Rohman's research (2021) shows that workload positively and significantly affects the performance of PT Honda Daya Anugrah Mandiri Sukabumi Branch employees. The same thing was expressed by research by Msuya and Kumar (2022), which states that workload has a positive and significant effect on the performance of bank employees in Tanzania. The results of this research mean that the increasing employee workload will cause employee performance to increase as well.…”
Section: Introductionmentioning
confidence: 52%
“…Additionally, Msuya and Kumar (2022) found that supervisory work-life support positively impacts employee performance in Tanzania's banking sector. Still, the correlation between workload and supervisory work-life support was negative and insignificant.…”
Section: Em-2024-6061mentioning
confidence: 99%
“…Training has recently become a critical theme in personnel organizational environments in Public Sector. In 2022, many organizations will prioritize culture through Sustainable Development Goals (SDG) (Msuya & Kumar, 2022). Supervisors implement the training programs based on the leaders' planning and managers' instructions to maintain and improve the competitiveness and productivity of their organizations (Palomino, Valdivia & García, 2022;Kumpikaitė-Valiūnienė et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In training management, feedback is frequently defined as the supervisor's ability to report on the most recent work performance, provide positive feedback, and convey ideas for improvement (Amoo & Adam, 2022;Msuya & Kumar, 2022;Tahiry & Ekmekcioglu, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation